Partager l’action paysagère avec des enfants pour interpeller le projet de paysage - Roxane Wormser (Projets de Paysage)
At the top of the political programme for the city of Lille is the "metamorphosis of the landscape" (in French, “metamorphose paysagère”) and with it the ambition to make Lille a "city planned with and for children". Since 2020, the political leadership of the Socialist majority, in dialogue with a strong environmentalist opposition, has led to a rethinking of established practices such as landscape planning, with a view to transforming the urban landscape environment. Although the word ‘landscape’ is used politically, the question that arises in Lille, as it does at a national level, is how it is translated into action (Besse, 2018). The aim here is to propose "a city planned with and for children" as a possible answer. In this context, the doctoral research takes the form of ‘experimental in-situ research’ (Nicolas-Le Strat, 2018) and engages within the processes of landscape projects in Lille designed with children to question ways of doing things as well as professional approaches. Drawing on the work of the philosopher Jean-Marc Besse, we look at two examples of projects implemented with children in Lille and we seek to make assumptions regarding possible movements or developments able to challenge urban planning practices and modify our relation to landscape planning.